2017
DOI: 10.1111/epi.13735
|View full text |Cite
|
Sign up to set email alerts
|

Scalp EEG Ictal gamma and beta activity during infantile spasms: Evidence of focality

Abstract: Objective We investigated temporal and spatial characteristics of ictal gamma and beta activity on scalp EEG during spasms in patients with West syndrome (WS) to evaluate potential focal cortical onset. Methods A total of 1033 spasms from 34 patients with WS of various etiologies were analyzed in video-EEG using time-frequency analysis. Ictal gamma (35–90 Hz) and beta (15–30 Hz) activities were correlated with visual symmetry of spasms, objective EMG (electromyography) analysis, and etiology of WS. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 40 publications
2
38
1
1
Order By: Relevance
“…[17][18][19][20] However, it is also possible that ES have a focal onset with rapid spread throughout the brain. 21 One study showed that infants with West syndrome and hypsarrhythmia had increased long-range EEG coherence in multiple frequency bands in sleep after onset of ES. 22 Another study showed that infants after ES onset had decreased longrange temporal correlation in the beta band of awake EEG.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] However, it is also possible that ES have a focal onset with rapid spread throughout the brain. 21 One study showed that infants with West syndrome and hypsarrhythmia had increased long-range EEG coherence in multiple frequency bands in sleep after onset of ES. 22 Another study showed that infants after ES onset had decreased longrange temporal correlation in the beta band of awake EEG.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In contrast to ECoG, the identification of HFOs with noninvasive scalp electroencephalography (EEG) has proven more challenging. Although several studies have linked beta, gamma, and ripple activity to hypsarrhythmia 8 and epileptic spasms 9,10 in West syndrome, and to the seizure-onset zones in focal epilepsy, 11 it is only recently that fast ripples (FRs) have been identified with the use of subdermal scalp electrodes in adults with epilepsy, 12 and with the use of standard scalp electrodes in children with epilepsy. 13 Nevertheless, it has not yet been established that the visual identification and quantification of scalp HFOs is reliable.…”
mentioning
confidence: 99%
“…Although prior studies have reported the presence of scalp EEG gamma band (30-80 Hz) and ripple band (80-250 Hz) activity in infantile spasms (Kobayashi et al, 2004;Kobayashi et al, 2015;Nariai et al, 2017), this is the first study to report that a fast ripple band (250-500 Hz) is seen on scalp EEG in children with infantile spasms. Recently our group reported for the first time that scalp EEG fast ripples could be seen in children with drug-resistant epilepsy with tuberous sclerosis complex (TSC) .…”
Section: Discussionmentioning
confidence: 56%
“…. The values range from -1 (values on the left hemisphere being disproportionally large) to +1 (values on the right hemisphere being disproportionally large) (Nariai et al, 2017). We compared the absolute asymmetric indices (abs AI) of HFOs (80-500 Hz) rate, MI of HFOs (80-500 Hz) & SWA (3-4 Hz and 0.5-1 Hz) between subjects with and without focal lesion on MRI.…”
Section: Fully Automated Analysis Of Cross-frequency Coupling Of Hfosmentioning
confidence: 99%
See 1 more Smart Citation